Promoting seed systems for stress-tolerant varieties at scale: Potential for bundling with insurance-advisory services - Cecchi, Francesco; Aredo, Samson Dejene; Kivuva, Benjamin; Omondi, Simon; Chegeh, Joseph; Tabalia, Amos; Kramer, Berber (International Food Policy Research Institute, 2019)
Smallholder farmers may suffer losses from ex-treme weather events, pests and disease. This is expected to worsen in the face of climate change. Natural disasters are a threat to food security not only ex post, by inducing farmers to sell their as-sets, keep children out of school or borrow at high rates; they also threaten livelihoods ex ante, by discouraging farmers from investing in high-return practices and technologies (Elbers et al., 2007). Fortunately, significant progress has been made in the past two decades in developing and releasing seeds with genetic traits that are more tolerant to weather shocks, pests and disease. These im-provements in seed technology are offering prom-ising pathways to improve farmers’ adaptive ca-pacity, increasing investments and thereby agri-cultural productivity (Emerick et al., 2016).